IMPLEMENTASI PERATURAN DAERAH KABUPATEN SAMBAS NOMOR 12 TAHUN 2019 TENTANG PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA MUARE ULAKAN(STUDI PADA PENINGKATAN AKSES AIR BERSIH DI KABUPATEN SAMBAS) - Dedi Zulkarnaen; Hasiah; Nilhakim (INTELIGENSIA MEDIA, 2025)
Access to clean water is a vital basic need for human life and an important indicator of public health and the achievement of Sustainable Development Goals (SDGs). In Sambas Regency, the availability of clean water still faces challenges, especially in rural and remote areas due to limited infrastructure, budget, and technical capacity. To overcome this, the Sambas Regency Government established Regional Regulation No. 12 of 2019 concerning the Tirta Muare Ulakan Regional Water Company as a strategic step in improving the equitable distribution of clean water services to the community. The focus of this study is: How is Regional Regulation No. 12 of 2019 concerning the Tirta Muare Ulakan Regional Water Company being implemented in Sambas Regency? What are the supporting and inhibiting factors in improving access to clean water in Sambas Regency? This study uses a qualitative method with an empirical juridical approach to analyse the implementation of Sambas Regency Regulation No. 12 of 2019 concerning the Tirta Muare Ulakan Regional Water Company. Data was obtained through observation, in-depth interviews with relevant parties, and documentation. The research location focused on Perumda Tirta Muare Ulakan and several villages that use clean water services. Data analysis techniques were carried out interactively through data reduction, data presentation, and conclusion drawing, as well as using source triangulation to ensure data validity. Based on the results of the research and discussion above, it was concluded that: The implementation of Sambas Regency Regulation No. 12 of 2019 concerning the Tirta Muare Ulakan Regional Water Company has shown progress, although its implementation has not been fully optimal. This Regional Company has succeeded in increasing the number of customers and expanding the clean water distribution network. The supporting factors are the existence of Regional Regulation No. 12 of 2019, which serves as the legal basis for the operations of Perumda Tirta Muare Ulakan, the support of the Regency Government through the RPJMD programme, capital participation, and cross-sectoral synergy in the development of clean water networks, especially in underserved areas. The inhibiting factors include technical constraints and infrastructure limitations, budget constraints and a lack of alternative funding support, the suboptimal implementation of local regulations due to a lack of understanding and socialisation, limitations in the number and competence of human resources, and a perception gap between officials and the community regarding service quality.